Proposta de indicadores para Smart Cities sustentáveis - João Vitor Souza Teixeira (2022)
Due to increasing search for shelter in cities by the population, several problems arise in areas like health, safety, environment, resources and infrastructure. In light of these problems, cities’ governments have been using tools to become smart, within the worldwide accepted concept of Smart City. The lack of metrics, identified in literature, to qualify a city as smart, as well as smart methodologies’ distancing from population’s quality of life, this study intends to analyze Smart City and sustainability indicators, in order to propose a functional indicators proposal for a smart sustainable city, in which improvement of citizens’ life quality is the main factor. To do that, Action Design Research method was used, divided into three steps. The first was a systematic literature review to define a concept for Smart City. Second step was an analysis through the indicators proposals’ gathered from specialists and organs, separating them by themes and determining their relevance through the frequency in which they appear in each model. The created proposal then, contains for each theme, indicators of Smart City, Sustainability and Quality of Life. In the third step, a comparison between the indicators and Smart City initiatives from thirty five cities around the world was performed to validate the model. The fourth and last step of the study is described as a proposal to evolve the research.